The application of green YPO4:Ce3+,Tb3+ and red LiLaO2:Eu3+ layers to remote phosphor LED - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Remote phosphor structure is commonly limited in color quality, but has greater luminous flux when comparing to structures with in-cup or conformal coating. From this dilemma, various researches with advance modifications have been proposed to perfect the chromatic performance of remote structure. In this research, we reach higher color quality by obtaining better values in quality indcators such as color rendering index (CRI) and color quality scale (CQS) with the dual-layer phosphor in our remote white light-emitting diodes (WLEDs). The idea is to ultize WLEDs with 7000 K correlated color temperature (CCT) and create dual-layer configuration with yellow phosphor YAG:Ce3+ under green phosphor YPO4:Ce3+,Tb3+ or red phosphor LiLaO2:Eu3+. After that, we search for suitable concentration of LiLaO2:Eu3+ for addition in order to acquire the finest color quality. The result shows that WLED with LiLaO2:Eu3+ has better CRI and CQS as the higher the concentration of LiLaO2:Eu3+, the larger CRI and CQS due to increased light scattered in WLEDs. Meanwhile, the green phosphor layer YPO4:Ce3+,Tb3+ give advantages to luminous flux. However, the reduction in luminous flux and color quality occurs when the concentration of LiLaO2:Eu3+ and YPO4:Ce3+,Tb3+ over increase. Results are verified by Mie theory and Beer’s Law and can be applied to practical manufacturing of high quality WLEDs.